(untitled) (Journal of Social Sciences Review, 2025)
The Audience engagement on digital media is a question in need for research introspection. The aim of the current research is to analyze audience engagement on vertical short-form videos and compare it with long-form horizontal videos in the scenario of podcasts in Pakistan. The data for the current research was collected from the leading Pakistani podcasters on YouTube and engagement of audience with their horizontal full length episodes and vertical short-form videos. The content analysis of their five most viewed podcasts of each podcaster and thematic analyses of experts interviews with the prominent podcasters and experts show that, vertical short-form entertainment with controversial and politically charged videos perform better than the knowledge-based videos. For knowledge-based videos, vertical formats need to be more digitally engaged.